PERAN PELABUHAN PERIKANAN SAMUDERA NIZAM ZACHMAN DALAM MENDUKUNG INDUSTRI TUNA (The Role of Nizam Zachman Oceanic Fishing Port to Support Tuna Industries) - Roma Y.F Hutapea; Iin Solihin; Tri Wiji Nurani (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2017)
ABSTRACTNizam Zachman Oceanic Fishing Port (OFP) has basic facilities, supportive facilities, and functional facilities that are needed for fishing activities in the port. The role of Nizam Zachman OFP as one of the largest tuna fishing ports in Indonesia is to support the availability of facilities required by each tuna industry stakeholders. The aimed of the research were to determine the role of Nizam Zachman OFP in providing support facilities and services in the activities of tuna fishing industries; and to determine the level of interest tuna stakeholders and level performance of Nizam Zachman OFP. Data analysis were carried out using a scoring method based on Ministry Regulation of Marine Affair and Fisheries number 8/PERMEN-KP/2012 about Fisheries Port then adapted to the conditions in the sites and analyze the level of interest and performance level with IPA (Importance Performance Analysis). The results showed that the role of Nizam Zachman OFP was good in production activities, infrastructure and public services, and there were still several service atributes performance that still have to be improved by the fishing port authority.Keywords: tuna industries, IPA, Nizam Zachman, fishing port role, scoring               ABSTRAKPelabuhan Perikanan Samudera Nizam Zachman memiliki fasilitas pokok, fasilitas penunjang, dan fasilitas fungsional yang sangat dibutuhkan dalam setiap aktivitas perikanan di pelabuhan. Peran PPS Nizam Zachman sebagai salah satu pelabuhan perikanan tuna terbesar di Indonesia dalam menunjang ketersediaan fasilitas diperlukan oleh setiap stakeholder industri tuna. Tujuan dari penelitian ini adalah untuk menentukan peran PPS Nizam Zachman dalam menyediakan fasilitas pendukung dan pelayanan dalam kegiatan industri perikanan tuna; dan menentukan tingkat kinerja PPS Nizam Zachman serta tingkat kepentingan  stakeholder tuna. Analisis data dilakukan dengan pembobotan atau scoring berdasarkan Peraturan Menteri Kelautan dan Perikanan Nomor 8/PERMEN-KP/2012 tentang Kepelabuhanan Perikanan yang kemudian disesuaikan dengan kondisi di lokasi penelitian.  Selanjutnya dilakukan analisis tingkat kepentingan dan kinerja dari PPS Nizam Zachman dengan menggunakan analisis IPA (Importance Performance Analysis). Hasil penelitian menunjukkan bahwa PPS Nizam Zachman berperan baik dalam aktivitas produksi, sarana prasarana dan pelayanan umum dan terdapat beberapa atribut pelayanan PPS Nizam Zachman yang masih harus ditingkatkan kembali kinerjanya.Kata kunci: industri tuna, IPA, Nizam Zachman, peran pelabuhan perikanan, skoring